PROGRAM INDONESIA SEHAT (PIS PK) TO FAMILY HEALTH STATUS - Darwis Darwis; Reka Lagora Marsofely; Wisuda Andeka; Lissa Ervina; Fikitri Marya Sari (Proceeding B-ICON, 2023)
Program Indonesia Sehat (PIS-PK) is a program implemented in all Puskesmas in Indonesia gradually since 2016 in the form of home visit activities aimed at increasing family access to comprehensive health services in order to realize a healthy Indonesia. This study aims to see the success of the achievements of the PIS-PK program in the form of health status categories and family health indexes, especially.  Of the three villages, there are a small number of unhealthy families. Healthy families, pre-healthy families. Methodology in the form of operational research is an integration of assistance with the Participatory Action research (PAR) approach with community-based surveys with interview techniques, population of 890 families, sample of 600 families with a quota sampling technique taken of 200 families per village. Data collection using interview techniques, observation and using questionnaires.  The data was analyzed with univariate presentation in the form of tables and graphs. The results of the health status research show that families have a small number of unhealthy families; almost half of them are healthy, and some families are pre-healthy; The implementation of PIS-PK has been carried out but has not been optimal. The results of this research can be used as teaching material become a reference by health workers, and input for the application of PIS-PK.